The Other Saudi Transformation. Issue 2 (11th May 2022) - Saab, Bilal Y.
Abstract: This article describes Saudi Arabia's historic and arduous journey to national‐defense transformation, launched around 2015. It analyzes the challenges and opportunities of defense reform in the kingdom while highlighting the role of the United States in this process. Last, the article discusses the future of US‐Saudi defense relations.